The protective effects of allopurinol against IL-17A-induced inflammatory response in mast cells. (January 2022) - Zhang, Zhaozhen; Ma, Xiaoran; Zha, Zhuqing; Zhao, Zhiwei; Li, Jitian
Graphical abstract: A schematic view of major signaling transduction pathways, including the conclusion that allopurinol diminishes IL-17A-induced inflammatory response in mast cells. Highlights: IL-17A expression was elevated in human RA synovium. Allopurinol inhibited IL-17A- induced TNF-α, IL-6, and IL-8 in HMC‑1 cells. Allopurinol reduced the expression of COX-2, iNOS, PGE2, and NO in HMC‑1 cells. Allopurinol attenuated IL-17A- induced oxidative stress. Allopurinol ameliorated the activation of the JNK/AP-1/NF-κB signaling pathway. Abstract: Rheumatoid arthritis (RA) is a common autoimmune disease in the elderly and it has been recently reported to be significantly associated with the activation of mast cells in joint tissues. IL-17A is a vital mediator that stimulates the activation of inflammation. Allopurinol is a classic agent for the suppression of uric acid production, recently reported to exert therapeutic effects on RA. In the present study, we investigated the regulatory effect of allopurinol against IL-17A-induced inflammatory response in mast cells and explored the potential mechanism of allopurinol on RA treatment. Firstly, we found that compared to normal synovium, IL-17A was significantly upregulated in the human RA synovium. IL-17A was used to stimulate an inflammatory state in mast cells in the absence or presence of allopurinol. We found that the production of inflammatory factors, PGE2, and COX-2 was significantly elevated in IL-17A-treated mast cells, accompanied by the activation of the iNOS/NO axis and the elevated secretion of ROS. After treatment with allopurinol, the elevated inflammation, activated COX-2/PGE2 and iNOS/NO axis, and oxidative stress were all dramatically alleviated. Mechanistically, the activated JNK/AP-1 and NF-κB pathways in IL-17A-treated mast cells were dramatically suppressed by the introduction of allopurinol. Taken together, our data reveal that allopurinol significantly alleviated the IL-17A-induced inflammatory response in mast cells.